Occurrence of Patulin and Polyphenol Profile of Croatian Traditional and Conventional Apple Cultivars during Storage - Ana-Marija Gotal Skoko; Ružica Vilić; Marija Kovač; Ante Nevistić; Bojan Šarkanj; Marta Lores; Maria Celeiro; Martina Skendrović Babojelić; Tihomir Kovač; Ante Lončarić (Foods, 2022)
Apples and apple-based products are among the most consumed fruits around the world. However, they are susceptible to infection with the fungi Penicilium expansum. In addition to the reduction of apple quality, secondary metabolism of this fungus produces a mycotoxin patulin that has a negative effect on human health. Currently, there is no available research in the literature on the resistance of Croatian traditional apple cultivars to contamination with P. expansum, and consequently, on the patulin content in apples and apple juice produced from those apples. Although the mechanism of apple resistance to fungal diseases has not yet been sufficiently investigated, some studies have shown that polyphenolic compounds have some impact on fungi growth. In order to contribute with new knowledge, this research deals with monitoring the growth of P. expansum on apples, patulin detection by LC/MS-MS, determination of polyphenol profile by validated HPLC method, and determining the effect of polyphenolic compounds on fungi growth and patulin production during apple storage. The results of this study have shown that Croatian traditional apple cultivars harvested from family farm Horvatić contain higher concentration of polyphenolic compounds and higher antioxidant activity. At the same time, they showed more resistance to infection by P. expansum than conventional ones. The higher content of dihydrochalcones and flavanols encouraged the biosynthesis of patulin in examined cultivars. However, the higher content of non-flavonoids such as 2-6 dimethoxybenzoic acid, 4-hydroxycinnamic acid and chlorogenic acid leads to decrease in content of patulin. In conclusion, it seems that content of polyphenols and patulin production are correlated.